The Perils of the Pandemic and India's Child Victims of Covid-19 - Sil, Suparba; Dhar, Ruby; Karmakar, Subhradip (International Journal of Child Health and Nutrition, 2021)
Aim: The following paper attempts to trace the impact of Covid-19 on the younger generation, mostly from economically underprivileged sections, by focusing on specific themes such as health, education, vulnerability to abuse, and violence. The paper tries to address how the pandemic has affected various dimensions of the lives of these younger generation-children and adolescents, alongside tracing the measures taken by the government in the fight against the virus. Methods: We curated the information based on credible data as published in leading news media, PMC published peer-reviewed materials Conclusions: The paper concludes with recommendations that a coherent government policy and the active participation of NGOs are needed to address the problem. The children's mental health needs to be dealt with utmost care at home, which will pave the way towards a better future for the younger generation during and after the pandemic.